Risk factors associated with maternal mortality. - Pinedo, Adolfo (2015)
OBJECTIVE. To identify risk factors associated to maternal mortality. DESIGN.- Cross sectional study of maternal mortality using the perinatal informatic system of the Obstetrics and Gynecology Department of Hospital Marla Auxiliadora of 21621 cases recorded from July 1, 1988 to December 31, 1992. We used a 2 x 2 table confidence interval 95% test to calculate relative risk (RR) taking social antroprometric, biologic and obstetric variables. RESULTS: The most important risk factors were: single status, no antenatal care, eclampsia, tuberculosis, puerperal infection, second trimester hemorrhage, preterm delivery, anemia, third trimester hemorrhage, septic abortion and urinary infection. CONCLUSION.- There is an association between maternal mortality and no antenatal care, single status and prevalent pathologies of pregnancy.